Advancing Theoretical Frameworks for Intersectional Research on Women in STEM. Issue 179 (22nd February 2019) - Gaston Gayles, Joy; Smith, Katie N.
Abstract: Research on women in STEM often silences the voices of minoritized populations, such as women of color, in part because the most commonly used theoretical frameworks do not center or contextualize their experiences. This chapter highlights the importance of critical perspectives and methodologies such as intersectionality in research design. We conclude with implications for using critical approaches to disrupt the status quo and advance minoritized populations in STEM.